2015
DOI: 10.1111/geob.12085
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of immigrants’ entry to homeownership in three nordic capital city regions

Abstract: The extent of homeownership among immigrants may be seen as an indicator of integration and as a determinant of ethnic residential segregation. Studies have shown differences in the determinants of homeownership between immigrants and natives, indicating that variation in homeownership is not only a function of differences in economic resources. These studies have largely focused on Anglo‐American contexts, using mostly cross‐sectional data. We apply survival analysis methods to analyse the determinants of ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
3
14
0
3
Order By: Relevance
“…As for the migration status, we find that those who migrated with their whole family have a high probability of owning a house, whereas sole migrants are unlikely to be homeowners. This finding is consistent with that of Alba and Logan (1992) and Kauppinen et al (2015), thereby confirming that housing needs also exert a large effect on homeownership. The migrants with permanent settlement intention have more likelihood to own a house, which is consistent with Tang et al (2017), which confirmed that migrants' settlement intention are positively related with the housing attainment of rural migrants' in the urban destinations.…”
Section: Estimation and Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…As for the migration status, we find that those who migrated with their whole family have a high probability of owning a house, whereas sole migrants are unlikely to be homeowners. This finding is consistent with that of Alba and Logan (1992) and Kauppinen et al (2015), thereby confirming that housing needs also exert a large effect on homeownership. The migrants with permanent settlement intention have more likelihood to own a house, which is consistent with Tang et al (2017), which confirmed that migrants' settlement intention are positively related with the housing attainment of rural migrants' in the urban destinations.…”
Section: Estimation and Analysissupporting
confidence: 87%
“…Household income is regarded as the most uniformly important determinant of homeownership, and families with high incomes are more likely to own a home than those with low income (Alba & Logan, 1992;Kauppinen et al, 2015). The homeownership gap between rural-urban and urbanurban migrants may vary across varied income groups.…”
Section: Data and Sample Descriptionmentioning
confidence: 99%
“…Bolt and van Kempen 2003). Spatial assimilation in the Nordic countries has mainly been studied from three perspectives: moving away from distressed immigrant-dense neighbourhoods (Vogiazides 2018;Macpherson and Strömgren 2013), moving to a neighbourhood considered higher status in socioeconomic terms (Wessel et al 2017;Magnusson Turner and Wessel 2013), and moving into homeownership as an indicator of integration (Magnusson Turner and Hedman 2014;Kauppinen, Andersen, and Hedman 2015;Kauppinen and Vilkama 2016). Most of these studies find some limited support for the spatial assimilation thesis 1 (although Wessel et al (2017) find a complete lack of spatial integration), but the studies that consider differences between immigrant groups find that variation between groups is insufficiently explained by socioeconomic attributes.…”
Section: Theoretical Background Previous Research and Hypothesesmentioning
confidence: 99%
“…This measure would likely require an urban planner and/or a city-housing engineer who could be consulted by community residents when needed to legitimise and stabilise the informal housing boom. The extent of homeownership among immigrants may be seen as an indicator of integration (Kauppinen et al, 2015), although integration and wealth acquisition is gradual and not every immigrant achieves this status (Maroto and Alysworth, 2016). Bearing this in mind, the national government should be prepared to view migrant homeownership both as a process and a long-term goal, in order to enable immigrant integration, upward mobility, and overall community development.…”
Section: Policy Changesmentioning
confidence: 99%